Fungal Endophytes from the Aerial Tissues of Important Tropical Forage Grasses Brachiaria spp. in Kenya - Ghimire, Sita R.; Njuguna, Joyce; Kago, Leah; Ahonsi, Monday; Njarui, Donald M. G. (International Livestock Research Institute, 2015)
Most, if not all plants in natural ecosystems are symbiotic with mycorrhizal fungi and/or fungal endophytes. This association between plant and fungi is believed to be over 400 million years old when plants first colonized the land (Redecker et al., 2000). These fungal symbionts play important roles on plant ecology, fitness, and evolution; shaping plant communities; and the community structure and diversity of associated organisms. The importance of fungal endophytes in cool season grasses production and effects of endophyte on the livestock health (Examples fescue toxicosis and ryegrass staggers) have been extensively investigated (Smith et al., 2009; di Menna et al., 2012). However, current understanding of fungal endophyte community of warm season grasses (including Brachiaria spp.) and the impact of these endophytes on livestock production is very limited. Therefore, this study aims to analyse fungal endophytes community inhabiting in the aerial tissues of important tropical grasses Brachiaria species from Kenya, an East African country representing place of origin for most of the Brachiaria species.